Exercise Prescription Using the Borg Rating of Perceived Exertion to Improve Fitness - Garnacho-Castaño, Manuel Vicente; Domínguez, Raúl; Muñoz González, Arturo; Feliu-Ruano, Raquel; Serra-Payá, Noemí; Maté-Muñoz, José Luis (International Journal of Sports Medicine, 2018)
The present study aimed to compare two fitness-training methodologies, instability circuit resistance training (ICRT) versus traditional circuit resistance training (TCRT), applying an experimental model of exercise prescription controlling and modulating exercise load using the Borg rating of perceived exertion. Forty-four healthy young adults age (21.6±2.3 years) were randomly assigned to three groups: TCRT (n=14), ICRT (n=14) and a control group (n=16). Strength and cardiorespiratory tests were chosen to evaluate cardiorespiratory and muscular fitness before and after the training program. In cardiorespiratory data, a significant difference was observed for the time effect in VO2max, peak heart rate, peak velocity, and heart rate at anaerobic threshold intensity (p<0.05) in the experimental groups. In strength variables, a significant Group x Time interaction effect was detected in 1RM, in mean propulsive power, and in peak power (p≤0.01) in the back squat exercise. In the bench press exercise, a significant time effect was detected in 1RM, in mean propulsive power, and in peak power, and a Group x Time interaction in peak power (all p<0.05). We can conclude that applying an experimental model of exercise prescription using RPE improved cardiorespiratory and muscular fitness in healthy young adults in both experimental groups.
Keywords: Instability training; Resistance training; Circuit training; BOSU; TRX; Free weights; machines